Analysis of The Implementation of Priority Services of The Ministry of ATR/BPN As an Effort To Modernize Land Services (Study At The Bungo Regency Land Office) - Novi Ardiansyah; Dwi Putranto Riau; Tukiyat (International Journal of Science and Environment (IJSE), 2026)
Modernization of land services is an important part of bureaucratic reform in improving the quality of public services that are faster, more transparent, and digital-based. This study aims to analyze the level of community interest and performance on the implementation of the seven priority services of the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN), determine the strategic position of services using Importance–Performance Analysis (IPA), and identify factors that affect community satisfaction through multiple linear regression. This study uses a quantitative approach with a survey method of 100 respondents selected using purposive sampling techniques. Data was collected through a Likert scale questionnaire and analyzed using descriptive analysis, Customer Satisfaction Index (CSI), IPA, and multiple linear regression. The results of the study showed that the average level of interest was 4.32 and the performance level was 3.89 in the good category. The CSI value of 77.80% shows that the community is in the satisfied category. The IPA analysis shows that transparency, speed of service, and professionalism of officers are in the quadrant of maintaining achievements, while the use of digital technology is the top priority for improvement. The regression results showed that the variables of transparency, speed, professionalism, and technology had a significant effect on public satisfaction with an R² value of 0.728. This study concludes that the implementation of ATR/BPN priority services has gone quite well, but it still needs improvements in digitalization and ease of procedures to achieve optimal services.